Pengaruh Metode Bernyanyi terhadap Penguasaan Kosakata Bahasa Inggris pada Siswa SD - Azzahra, Salsabilla (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research aims to evaluate the influence of the singing method on English vocabulary mastery in elementary school students. The research method employs an experimental approach with control and treatment groups. Students in the treatment group engage in vocabulary learning sessions through singing, while the control group follows a conventional approach. Data is collected through vocabulary tests before and after the intervention. The data analysis results show a significant improvement in vocabulary mastery in the treatment group compared to the control group. Singing method proves effective in enhancing students' learning motivation, strengthening vocabulary retention, and stimulating active engagement in English learning. These findings have positive implications for the development of teaching strategies focusing on creative and interactive elements, particularly in the context of language learning at the elementary school level.